Persistency in the NEET state: a longitudinal analysis. (9th August 2019) - Contini, Dalit; Filandri, Marianna; Pacelli, Lia
ABSTRACT: This article addresses the NEET phenomenon in a longitudinal perspective, by examining the case of Italy, a country experiencing one of the highest and increasing NEET shares in the EU. We exploit the longitudinal sample of the 2008-2011 EU-SILC data, providing self-declared information on individuals' educational and occupational status on a monthly basis for 4 years. Firstly, we propose a classification of individual histories in education, employment and the NEET states. According to our estimates, more than 40% of the Italian young people report being NEET for at least 13 months out of 48, and more than 10% for (almost) the entire period. Secondly, we examine the composition of the NEET groups and draw a long-term NEET risk profile for individuals from different sociodemographic groups. Thirdly, we examine the longitudinal histories by distinguishing between unemployment and inactivity spells. Our findings show that the NEET phenomenon among Italian young adults is largely an issue of unemployment. The only exception is represented by Italian older females with children, the majority of which portrays themselves as inactive. Still, a sizable portion of these women define themselves as being mainly 'unemployed' instead of 'performing domestic tasks', indicating an unsatisfied wish or need to work.